The Evolution of Brand Activism Research: A Bibliometric Analysis - Loso Judijanto (West Science Business and Management, 2025)
Brand activism has emerged as a prominent phenomenon in contemporary marketing and management research, reflecting the growing expectation that brands act as social and political actors beyond their traditional economic roles. As scholarly interest in this topic has expanded rapidly, the literature has become increasingly diverse and fragmented across disciplines, themes, and methodological approaches. This study aims to systematically examine the evolution of brand activism research through a comprehensive bibliometric analysis. Using data retrieved from the Scopus database, the study analyzes publication trends, citation patterns, influential authors and institutions, country collaborations, and thematic developments using VOSviewer. The findings reveal that brand activism research has evolved from early normative and ideological debates toward a more consolidated and empirically grounded field, with growing emphasis on social media, consumer activism, authenticity, corporate and CEO activism, and branding outcomes such as loyalty and brand equity. The results also indicate a dominance of transatlantic research networks, alongside emerging contributions from developing economies. By mapping the intellectual structure and thematic trajectory of brand activism research, this study provides an integrative overview of the field, identifies key research clusters and gaps, and offers a foundation for future theoretical development and empirical investigation.